Application of Hydrodynamic Potential Analysis to Investigate Possibility Reservoir Connectivity between Neighboring Gas Fields - Tri Firmanto; Muhammad Taufiq Fathaddin; R. S. Trijana Kartoatmodjo (Penerbitan Universitas Trisakti, 2019)
T field is a producting gas field in North Bali PSC, which currently producing 210 mmscfd from paciran sand stone formation. Paciran formation extends more than 20 km across the PSC area, which consists of 3 developed gas fields and one potential development field. The flowing material balance analysis conducted on T field suggests possibility of reservoir connectivty between this field and its neighboring fields. Even though each field is already have a well defined Gas Water Contact, a thorough investigation was done using hyrdodynamic potential analysis to see if theres any hydrodynamic potential that allowed connectivity between these fields, and enable tilted contact occurred between these field. Using pressure data taken from each fields exploration wells the analysis can be conducted that conclude that there is an existing hydrodynamic potential between gas fields in paciran formation. A review on the tilted contact analysis concludes that the existing hydrodynamic potential is not enough to tilt the contact as per actually observed contact.